(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the role of innovation in increasing the profit of joint-stock companies, as well as highlights the ways to use the “product-market” matrix and the advantages of using the scoring model in the development of company innovation.